Allies / [compact disc, unabridged] - Golden, Christie (Star wars, fate of the Jedi., 2010)
What began as a quest for truth has become a struggle for survival for Luke Skywalker and his son, Ben. They have used the secrets of the Mindwalkers to transcend their own bodies and speak with the spirits of the fallen, risking their very lives in the process. They have faced a team of Sith assassins and beaten the odds to destroy them. And now the death squad's sole survivor, Sith apprentice Vestara Khai, has summoned an entire fleet of Sith frigates to engage the embattled father and son. But the dark warriors come bearing a surprising proposition that will bring Jedi and Sith together in an unprecedented alliance against an evil more ancient and alien than they can imagine.